P1776HLA TYPING BY NGS ENHANCES MISMATCH DETECTION IN LIVING KIDNEY TRANSPLANTATION. (6th June 2020) - Pehnke, Sarah; Lindner, Tom H; Popp, Bernt; Doxiadis, Ilias; Landgraf, Ramona; Lehmann, Claudia; Halbritter, Jan; Münch, Johannes
Abstract: Background and Aims: Antibody mediated rejection (ABMR) due to the development of donor specific HLA antibodies is the most common cause for graft loss in kidney transplant recipients. Therefore, a low count of HLA mismatches is favorable in the course of transplantation. Hitherto, several techniques for HLA typing have been adapted in parallel, e.g. serological or low-resolution PCR. In this single-center study, we aimed to perform "HLA re-typing" by next generation sequencing (NGS) in a living kidney transplant cohort (n=143), in order to identify HLA mismatches in donor/recipient pairs, that were missed by previous HLA typing methods. Method: We isolated DNA of 102 donor/recipient pairs, that received a living kidney transplantation at the University Hospital Leipzig (Germany) between 1998 and 2018, and performed long range PCR of all known HLA loci. Using these NGS results, we compiled a genomic HLA mismatch formula. We evaluated, if genomic HLA typing identifies more HLA mismatches compared to the results of previous HLA typing methods, that were recorded in the Eurotransplant database for our donor/recipient pairs. Results: By genomic HLA typing, we were able to identify HLA mismatches in 10.2 % of donor/recipient pairs, that have been missed by previous methods. In our cohort, we recognized most mismatches in the DRB1 locus, that were missed with other HLA typing techniques. Conclusion: Our results suggest, that genomic HLA typing can be more precise in detecting HLA mismatches in donor recipient/pairs. Especially in the course of living kidney transplantation, a higher accuracy in HLA typing might enhance donor selection. Furthermore, accurate HLA typing can influence graft management in the course of ABMR, as it may improve the detection of donor specific HLA directed antibodies.